(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
In the given article we had done the in-vitro anti-diabetics analysis of the plant Alternantheraficoidea and Polianthes tuberosa with their phytochemical analysis we had first of all collected the plantand washed it properly with water then after we had washed several times with different solvent after thatwe had taken its ash value and foreign mater then after we had investigated it. Throughout the wholestudy we find the result more satisfying and it is also suggestive for further investigation.